A Framework for Understanding Systems Principles and Methods. Issue 3 (14th November 2018) - Rousseau, David
ABSTRACT: Systems engineering is increasingly challenged by the rising complexity of projects undertaken, resulting in increases in costs, failure rates, and negative unintended consequences. This resulted in calls for more scientific principles to underpin the methods of systems engineering. In this paper, it is argued that our ability to improve systems engineering's methods depends on making the principles of systemology, of which systems engineering is a part, more diverse and more scientific. An architecture for systemology is introduced, which shows how the principles of systemology arise from interdependent processes spanning multiple disciplinary fields, and on this basis a typology is introduced, which can be used to classify systems principles and systems methods. This framework, consisting of an architecture and a typology, can be used to survey and classify the principles and methods currently in use in systemology, map vocabularies referring to them, identify key gaps, and expose opportunities for further development. It may thus serve as a tool for coordinating collaborative work towards advancing the scope and depth of systemology